2013
DOI: 10.3109/00365548.2013.776700
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid chemokine CXCL13 in the diagnosis of neuroborreliosis in children

Abstract: In LNB, the production of CXCL13 in CSF seems to precede antibody production. Assessment of CSF CXCL13 may improve the diagnostics for children with possible LNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
2
19
3
Order By: Relevance
“…However, Bremell et al showed that CSF CXCL13 was not increased in HIV-infected patients (15), and we did not observe elevated CSF CXCL13 concentrations in the HIV-and T. pallidum-coinfected control group with a negative CSF-RPR result. Even though the effect of HIV alone was not proven in our study, Bremell et al (15) data may suggests that there is an added CSF CXCL13 release in neurosyphilis patients coinfected with HIV, 16 (16) hence the observed added benefit of CSF CXCL13 in HIV-infected patients in diagnosing neurosyphilis. However, we cannot strictly exclude other causes for high or detectable CXCL13.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, Bremell et al showed that CSF CXCL13 was not increased in HIV-infected patients (15), and we did not observe elevated CSF CXCL13 concentrations in the HIV-and T. pallidum-coinfected control group with a negative CSF-RPR result. Even though the effect of HIV alone was not proven in our study, Bremell et al (15) data may suggests that there is an added CSF CXCL13 release in neurosyphilis patients coinfected with HIV, 16 (16) hence the observed added benefit of CSF CXCL13 in HIV-infected patients in diagnosing neurosyphilis. However, we cannot strictly exclude other causes for high or detectable CXCL13.…”
Section: Discussioncontrasting
confidence: 59%
“…Even though CSF CXCL13 concentration is not a confirmatory test, we assume on the basis of serological syphilis and pathogenesis of CXCL13 that CSF CXCL13 concentration can contribute to the diagnosis of neurosyphilis. Furthermore, the use of CSF CXCL13 concentration for the diagnosis of neurological infections with spirochetes, such as neuroborreliosis and also neurosyphilis, has been shown before (13,16). However, the current study demonstrates an added value of CXCL13 concentration as a marker in the diagnosis of neurosyphilis, which increases in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 57%
“…The B‐cell‐attracting chemokine CXCL13 has in previous studies been shown to be reliably elevated in the CSF of patients with early LNB, and furthermore, to decrease rapidly after antibiotic treatment . Thus, analysis of CXCL13 in the CSF may be helpful in AI‐negative patients with possible early LNB, as well as a marker for active disease and in control of therapeutic response in AI‐positive patients.…”
mentioning
confidence: 98%
“…However just as in neurosyphilis, since active infection is almost always accompanied by a CSF pleocytosis, elevated CSF protein or both, these non-specific markers can be used to judge whether infection is currently active. Some studies further suggest that measurement of CSF CXCL13, though not necessarily specific for Lyme disease [26], may provide an additional useful marker of disease activity [27][28][29].…”
Section: Diagnosismentioning
confidence: 99%